2009
DOI: 10.1080/20786204.2009.10873831
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of sharps injury to health care workers at Witbank Hospital

Abstract: Background: The aim of this study was to identify procedures, areas of activity, occupational groups and other variables that carry a high risk of transmission of bloodborne infections from patients to healthcare workers (HCWs) at Witbank Hospital.Method: This was a descriptive cross-sectional study, conducted among HCWs of Witbank Hospital who were directly involved in patient care over the two-year period under consideration (1.01.03 -31.12.04). A directed questionnaire was used to carry out the study.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
14
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 8 publications
7
14
2
Order By: Relevance
“…These findings are consistent with findings reported elsewhere about the sharps injuries in ophthalmic practice and surgical settings [3,[12][13][14]. This is merely a reflection of the main function of the speciality as the surgical component dominates the workloads.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings are consistent with findings reported elsewhere about the sharps injuries in ophthalmic practice and surgical settings [3,[12][13][14]. This is merely a reflection of the main function of the speciality as the surgical component dominates the workloads.…”
Section: Discussionsupporting
confidence: 82%
“…The needle whether suture needle or hollow-bore needle was strikingly the major injury tool which is consistent with finding in surgical and non-surgical health settings [2,[7][8][9][10]12,16] where the needle was the most frequent injury tool. The needle was the most frequent injury tool among all groups of HCWs and the nurses comprised the majority of HCWs injured by needle due to the diversity of their work, which involves usage of needle in the ward, the theatre, the clinic and the laboratory.…”
Section: Discussionsupporting
confidence: 66%
“…In this study, the majority of HCWs who reported to have sustained needle stick and sharps injury were nurses 80(40.4%), and this is in agreement with a study done in Pretoria [25], and much higher than studies done in Kenya [19] and Nigeria [17]. The possible difference may be due to the ratio of nurse to people is not proportional as set by the WHO.…”
Section: Magnitude Of Needle Sticks and Sharps Injuriessupporting
confidence: 90%
“…Be that as it may, and for the relatively small sample size, 56.9% represents more than a half of the sample size. Global literature has reported a wide range, between 24% and 84% of sharp injuries [12,20,[28][29][30]. Occupational exposure to blood and body fluids is very high among HOs, and this is important because of the danger of cross-infection that this may pose.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is growing evidence that many cases of occupational exposure to blood and body fluids through needlestick and sharps injuries go unreported [8][9][10] and if reported, they would increase the incidence beyond the reported 100 million annual cases of occupational hazards. One group of medical professionals that are perhaps most vulnerable are the new practitioners, known as House Officers or Interns [11,12]. House Officers (HOs) as used in this study are the newly qualified medical or dental doctors (recent graduates of medical or dental schools) who are employed by hospitals to carry out various procedures, many of which are done under supervision.…”
Section: Introductionmentioning
confidence: 99%